1976
DOI: 10.1083/jcb.69.1.210
|View full text |Cite
|
Sign up to set email alerts
|

Intranuclear complexes in a copper-tolerant green alga.

Abstract: The results of ultrastructural studies and transmission electron microscope microanalysis of two Scenedesmus strains experimentally exposed to copper sulfate are presented. A fine-structural examination of the cells revealed the presence of nuclear inclusions in the form of central dense-core complexes. Cytoplasmic structures resembling the intranuclear inclusions were occasionally found in the cells. TEM-X-ray microanalysis of these structures has provided evidence that the inclusions contain copper. It is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Although it is sometimes difficult to distinguish between the two phenomena, there is an increasing body of evidence for rapid genetic evolution resulting from a variety of anthropogenic stresses. Metal tolerance in algae has been described by Butler et al (1980), Chapman (1985, Fitzgerald and Faust (1963), Klerks and Weis (1987), Silverberg et al (1976), Stockner and Antia (1976), and Stokes and Dreier (1981). Soldo and Behra (2000) exposed a natural periphyton population from the river Glatt (Switzerland) during 16 wk to various Cu concentrations (ranging from 0.05 to 5 µM) and observed an increased Cu tolerance in populations previously exposed to Cu.…”
Section: Acclimation and Adaptation Under Laboratory Conditionsmentioning
confidence: 92%
“…Although it is sometimes difficult to distinguish between the two phenomena, there is an increasing body of evidence for rapid genetic evolution resulting from a variety of anthropogenic stresses. Metal tolerance in algae has been described by Butler et al (1980), Chapman (1985, Fitzgerald and Faust (1963), Klerks and Weis (1987), Silverberg et al (1976), Stockner and Antia (1976), and Stokes and Dreier (1981). Soldo and Behra (2000) exposed a natural periphyton population from the river Glatt (Switzerland) during 16 wk to various Cu concentrations (ranging from 0.05 to 5 µM) and observed an increased Cu tolerance in populations previously exposed to Cu.…”
Section: Acclimation and Adaptation Under Laboratory Conditionsmentioning
confidence: 92%
“…Subsequent to chronic exposure to Cu, C. vulgaris are known to have developed tolerance, thereby, showing an increased ability to prevent Cu enrichment (Lindestrom, 1980). Silverberg et al (1976) reported Scenedesmus spp. grown in media containing 1 mg l À 1 copper to become copper-tolerant, wherein they contained 0.76 mg Cu g À 1 dry weight; these authors also reported that the non-tolerant Scenedesmus spp.…”
Section: Tolerance Capacitymentioning
confidence: 97%
“…The Cu-rich complexes identified within the nuclei of Cu-tolerant strains of the green algae Scenedesmus (SILVERBERG et al 1976) may also be proteins of the metallothionein type. Cd-binding proteins have been isolated from Anacystis nidulans (MACLEAN et al 1972), soybean (CASTERLINE andBARNETT 1977), tomato (BARTOLF et al 1980), and Phaseolus vulgaris (WEIGEL and JAGER 1980).…”
Section: D) Compartmentation Of Cu In Insoluble Complexesmentioning
confidence: 98%